Duodenal atresia: prenatal ultrasonic evidence - Kocakoç, Ercan; Kiriş, Adem; Kazez, Ahmet (My University, 2003)
[Abstract Not Available]
Duodenal atrezi: prenatal US tani.
Keywords: Adult; Duodenal Obstruction; Female; Fetal Diseases; Humans; Intestinal Atresia; Pregnancy; Ultrasonography, Prenatal; adult; article; case report; duodenum obstruction; echography; female; fetus disease; human; intestine atresia; pregnancy; prenatal development